Magnetic Mesoporous Silica for Targeted Drug Delivery of Chloroquine: Synthesis, Characterization, and In Vitro Evaluation - Rafaela de Andrade; Rita de Cássia dos Reis Schmidt; Leonardo Santos Gomes; Legna Colina-Vegas; Ruth Hinrichs; Marcos Antônio Zen Vasconcellos; Tania Maria Haas Costa; Monique Deon; Wilmer Villarreal; Edilson Valmir Benvenutti (MDPI AG, 2024)
Malaria is a dangerous tropical disease, with high morbidity in developing countries. The responsible parasite has developed resistance to the existing drugs; therefore, new drug delivery systems are being studied to increase efficacy by targeting hemozoin, a parasite paramagnetic metabolite. Herein, magnetic mesoporous silica (magMCM) was synthesized using iron oxide particles dispersed in the silica structure for magnetically driven behavior. The X-ray diffractogram (XRD) and Mössbauer spectra show patterns corresponding to magnetite and maghemite. Furthermore, Mössbauer spectroscopy revealed superparamagnetic behavior, attributed to single magnetic domains in particles smaller than 10 nm. Even in the presence of iron oxide particles, the hexagonal structure of MCM is clearly identified in XRD (low-angle region) and the channels are visible in TEM images. The drug chloroquine (CQ) was encapsulated by incipient wetness impregnation (magMCM-CQ). The N2 adsorption-desorption isotherms show that CQ molecules were encapsulated in the pores, without completely filling the mesopores. BET surface area values were 630 m2 g−1 (magMCM) and 467 m2 g−1 (magMCM-CQ). Encapsulated CQ exhibited rapid delivery (99% in 3 h) in buffer medium and improved solubility compared to the non-encapsulated drug, attributed to CQ encapsulation in amorphous form. The biocompatibility assessment of magMCM, magMCM-CQ, and CQ against MRC5 non-tumoral lung fibroblasts using the MTT assay after 24 h revealed no toxicity associated with magMCM. On the other hand, the non-encapsulated CQ and magMCM-CQ exhibited comparable dose-response activity, indicating a similar cytotoxic effect.